Ultrasound-Navigated Multiple Hippocampal Transections: An Anatomical Study - Sroubek, Jan; Kramska, Lenka; Cesak, Tomas; Amlerova, Jana; Keller, Jiri; Vojtech, Zdenek (Journal of neurological surgery. Part A, Central European neurosurgery, 2024)
BACKGROUND: Multiple hippocampal transection (MHT) is a surgical technique used for the treatment of drug-resistant mesial temporal lobe epilepsy in situations where standard procedures would pose a high risk for memory deterioration. During MHT, the longitudinal fibers of the hippocampus, implicated in epilepsy spreading, are interrupted, while the transverse memory circuits are spared. The extent of MHT is governed by intraoperative electrocorticography; abolition of epileptic discharges serves as an end point to terminate the transection. In other words, the aim of MHT is not the anatomical completeness of hippocampal transection. In contrast, we hypothesize that only the complete transection of hippocampal cross-section is needed to durably terminate epilepsy, avoiding possible postoperative reorganization of longitudinal pathways. Here, we report an anatomical study designed to evaluate the feasibility of complete transection of hippocampus with the aid of ultrasound neuronavigation and we propose new instruments to reach this goal. METHODS: Five cadaveric brains were analyzed in this study. MHT was performed on both sides of each brain either with or without ultrasound neuronavigation. The percentage of transected cross-section of the hippocampus was measured using magnetic resonance imaging (MRI) and both sides were compared. RESULTS: The ultrasound-guided MHTs were more likely to achieve complete hippocampal transection compared with the nonnavigated MHT transection (73 vs 58%; p < 0.01). Our study also allowed us to propose specialized transectors to minimize invasivity of this procedure. CONCLUSION: Completeness of MHT can be better reached with the aid of an ultrasound neuronavigation system; modified instruments for this procedure were also designed.
Keywords: Drug Resistant Epilepsy; neuronavigace; Epilepsy, Temporal Lobe; Cadaver; neurochirurgické výkony; Hippocampus; Neurosurgical Procedures; Humans; Magnetic Resonance Imaging; lidé; Neuronavigation; epilepsie temporálního laloku; magnetická rezonanční tomografie; mrtvola; hipokampus; refrakterní epilepsie